Sirt1 Regulates Oxidative Stress in Oxygen-Glucose Deprived Hippocampal Neurons - Shi, Lina; Zhang, Jing; Wang, Yan; Hao, Qingfei; Chen, Haoming; Cheng, Xiuyong (Frontiers in Pediatrics, 2020)
Oxidative stress is an important mechanism of neonatal hypoxic-ischemic brain damage. Sirtuin1 (Sirt1) is a deacetylase that depends on NAD+ which has an important role in antioxidant metabolism. Furthermore, peroxisome proliferator-activated receptor γ-coactivator 1α (PGC-1α) is a key regulator of mitochondrial oxidative stress, which is regulated by Sirt1. Here, we investigated the role of Sirt1 in the pathogenesis of brain injury after modulating its activity in primary cultured hippocampal neurons. Our study shows that the expression of Sirt1 was down-regulated after oxygen-glucose deprivation. Activation of Sirt1 with resveratrol improved cell resistance to oxidative stress, whereas inhibition of Sirt1 with EX527 significantly reduced cell viability after cellular oxidative stress. Our study also shows that activation of Sirt1 with resveratrol exerts its antioxidant effect by regulating the expression of PGC-1α. In contrast, application of EX527 decreased the expression of PGC-1α. In summary, these results confirmed that Sirt1 is a potent protective factor for neurons subjected to oxidative stress and the protective effect of Sirt1 is attributed to its regulation of PGC-1α.